Effectiveness of Knowledge Management on Knowledge and Management of Hypertension in Elderly - Thongcharoen, Vilaivan; Ronnarithivichai, Chantana; Peachpansri, Somjin; Boonchun, Natsurang; Vanicharoenchai, Vorawan (Nursing Science Journal of Thailand, 2011)
Purpose: This study aimed to evaluate the effects of theknowledge management on knowledge and management ofhypertension, and to synthesize good practices in managing bloodpressure of the hypertensive elderly patients. Designs: Participatory action research. Methods: A purposive sampling of 30 elders who hadhypertension and were able to control BP ≤ 140/90 mm Hg was recruited. The measurements included knowledge and behavior onhypertensive management questionnaires, and the interviewguides for the focus group and in-depth interviews. Theparticipants attended the meeting for community of practice inthe knowledge management process once a month for six months. Main findings: The results showed that knowledge managementprocesses effect on health problem management of elders withcontrolled hypertension in both knowledge and behavioralpractices especially in diet, observation of symptoms andproblem-solving and overall behaviors (p < .05). The guidelines ofgood practice to control participants’ blood pressure were adheredto, including basic exercise principles, avoidance of sugar, fat, andsalt in their diet, eating more fruit and vegetables, stressmanagement, taking medication, living in a good environmentwithout air pollution, and observation of symptoms. Conclusion and recommendations: The findings recommendedthat the Community of Practice for these elders with hypertensionbe developed and maintained their activities to sustainablymanage their hypertensive problems.